The Influence of Managerial Ownership and Firm Size on Corporate Environmental Disclosure - Nikmatus Sholikha; Ibnu Al Saudi; Hilmi Satria Himawan (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2023)
Companies in the primary and chemical industry sector are involved in producing chemical substances. These industries process raw materials obtained through mining, agriculture, and other sources into materials, chemical substances, and chemical compounds to become final and intermediate products used in different industries. This study aims to investigate and prove the effect of managerial ownership and firm size on corporate environmental disclosure. The ratio used in this study is the percentage of managerial shares, total company assets, and corporate environmental disclosure reports. This is quantitative research with the type of ex-post facto (cause and effect) research. The population of this study is a manufacturing company in the primary and chemical industry sector listed on the Indonesia Stock Exchange. The sample was selected using a purposive sampling method to obtain ten samples of primary and chemical industry companies from 2017 to 2021. The data analysis method used in this study was Eviews 12 software. The results of the model estimation test show that the selected model, the Random Effect Model (REM), becomes a regression analysis method. This study indicates that partially managerial ownership does not significantly affect environmental disclosure. Moreover, firm size gives positive findings and significantly affects corporate environmental disclosures. The R-Square value of this study is only 3.8% because the results of the F test state that managerial ownership and simultaneous firm size do not significantly affect corporate environmental disclosures.